Developing English Teaching Materials: Vocational Based-Learning for Chemical Engineering students - Achmad Sjaifullah; Abd Muqit (Belantika Pendidikan, 2022)
The materials needed by vocational education must be fairly different from the university students. The needs are based on the actual phenomenon of working situation. The reasearch tries to develop the English materials for vocational education based on learning activity at chemical Enginering State Polytechnic of Malang. It has been known that the present materials must the updated based on the developing need of industry. The method used was descriptive. It uses nine steps to do this research. These nine steps are investigating interesting topic, exercises, intruction, exploring the level of difficulty, selecting the best topics, and evaluating the exercises of the student book. It is all done by giving questionaire to the users and to experts. This research found out that the developing of English teaching materials based on vocational domain is suited with the updated needed by the students and by industries where the students commonly work.  It is in line with the students needs and curriculum applied in vocational education. This research gives a solution and ways of teaching models for vocational institution that are in line with the students, industry, and curriculum needs, and this can be applied wholly in Indonesian vocational institution.